A multi-site randomized clinical trial to reduce suicidal ideation in suicidal adult outpatients with Major Depressive Disorder: Development of a methodology to enhance safety. (June 2015) - McCall, William Vaughn; Benca, Ruth M; Rosenquist, Peter B; Riley, Mary Anne; Hodges, Chelsea; Gubosh, Brittany; McCloud, Laryssa; Newman, Jill C; Case, Doug; Rumble, Meredith; Mayo, Mark; White, Kaitlin Hanley; et al.
Background/aims: Suicide is a major public health concern, yet there are very few randomized clinical trials that have been conducted to reduce suicidal ideation in patients at risk of suicide. We describe the rationale and refinements of such a trial that is designed to assess the effect of a hypnotic medication on suicidal ideation in adult outpatients currently experiencing suicidal ideation. Methods: "Reducing Suicidal Ideation Through Insomnia Treatment" is a multi-site randomized clinical trial that includes three recruiting sites and one data management site. This 4-year study is in its second year of recruitment. The purpose of the study is to compare hypnotic medication versus placebo as an add-on treatment to a selective serotonin reuptake inhibitor as a means of reducing suicidal ideation in depressed adult outpatients with insomnia and suicidal ideation. The safety features of the study follow the 2001 National Institutes of Health guidelines for studies that include patients at risk of suicide. Results: In total, 584 potential participants have undergone telephone screening; 67% of these failed the phone screen, most often due to an absence of expressed suicidal ideation (26% of the telephone screen fails). A total of 115 people appeared for a face-to-face baseline assessment, and 40 of these had completed a taper off of their ineffective psychotropic medications before the baseline assessments. In all, 64% of those who completed baseline assessments failed to proceed to randomization, most commonly because of no clinically significant suicidal ideation (51% of those excluded at baseline). One participant was offered and accepted voluntary psychiatric hospitalization in lieu of study participation. Thus far, 40 participants have been randomized into the study and 88.7% of scheduled visits have been attended, with 93.8% adherence to the selective serotonin reuptake inhibitor and 91.6% adherence to the randomized hypnotic versus placebo. None of the randomized participants have required hospitalization or had a suicide attempt. Conclusion: By carefully considering the inclusion and exclusion criteria and other safety features, the safe conduct of randomized clinical trials in suicidal adult patients is possible, including the inclusion of participants who have undergone a prescribed tapering off of psychotropic medications prior to baseline assessment.